Pernikahan Nasbiyah Sayyid dan Syarifah (Studi Living Hadits di Kampung Arab, Kademangan, Bondowoso) - Muhammad Khusna Amal; Nawirah Ali Hajjaj (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2021)
In the Arab village of Bondowoso, precisely on the streets of HOS Cokroaminoto and KH. Asy'ari still maintains the custom of nasbiyah marriage. The focus of the research in this study is: what is the meaning of marriage according to the Alawite Arabs; why do 'alawiyyin Arabs in the past make a tradition of 'alawiyyin' Arab marriages; how the Alawite Arabs maintain the tradition of marriage between Alawite Arabs; and what are the views of the Alawite Arabs on the hadiths that prioritize their religious aspects. The results of this study are 1) Marriage is a physical and spiritual bond between a man and a woman to fulfill the purpose of married life as husband and wife by fulfilling the requirements and pillars that have been determined by Islamic law. 2) nasab is a descendant, so nasbiyah marriage is a marriage carried out by sayyid (Arabic man) and Syarifah (Arabic woman) to maintain the descendants that continue to the Prophet Muhammad. 3) it has become a tradition for Arabs to marry fellow Arabs as well, namely the Alawite group, besides that this tradition usually occurs because of the element of matchmaking by both parties, there is even a close family relationship between the bride and groom. 4) the view of the Arab Alawiyyin on the hadith prioritizes the religious aspect, if the lineage is good then the religion will be good too.